Dietary supplementation of Chinese herbal medicines enhances the immune response and resistance of rainbow trout (Oncorhynchus mykiss) to infectious hematopoietic necrosis virus - Wang, Qi; Pan, Yucai; Huang, Jinqiang; Li, Yongjuan; Wu, Shenji; Zhao, Lu; Sun, Tongzhen; Kang, Yujun; Liu, Zhe (Frontiers in Veterinary Science, 2024)
Rainbow trout is a widely farmed economical cold-water fish worldwide, but the prevalence of infectious hematopoietic necrosis virus (IHNV) presents a severe risk to the aquaculture industry, resulting in high mortality and huge economic losses. In this study, the impacts of different concentrations (0, 10, 20, and 30 g/kg) of Chinese herbal medicine mixture (CHMM) on the immune response and resistance of rainbow trout to IHNV infection were evaluated. The results show that CHMM noticeably increased (P < 0.05) T-SOD, CAT, AST, ALT, ACP, and AKP activities and decreased MDA content. NF-κB, TNF-α, IFN-β, IL-1β, JAK1, HSP70, and HSP90 expressions were significantly upregulated (P < 0.05) in all CHMMs, while SOCS2 expression was downregulated (P < 0.05). Following infection with IHNV, feeding rainbow trout with varying amounts of CHMM resulted in noticeably increased (P < 0.05) T-SOD, ACP, and AKP activities and significantly decreased (P < 0.05) MDA content and AST and ALT activities. TNF-α, IFN-β, IL-1β, HSP70, and HSP90 expressions were significantly upregulated (P < 0.05) in all CHMMs, while the expressions of JAK1 and SOCS2 were downregulated. The expression level of the IHNV G protein gene at a dosage of 20 g/kg was notably lower than that of the other CHMM feeding groups. This study provides a solid scientific basis for promoting CHMM as an immunostimulant for boosting antiviral immunity in rainbow trout.